KUALITAS AUDIT EKSTERNAL, KUALITAS INFORMASI AKUNTANSI, KEKUATAN LABA, DAN KINERJA PERUSAHAAN BERBASISKAN NILAI-NILAI KEISLAMAN (STUDI EMPIRIS PADA PERUSAHAAN YANG MASUK DALAM INDEKS SAHAM SYARIAH INDONESIA (ISSI)) - Aspirandi, Rendy Mirwan; Satoto, Eko Budi (Universitas Muhammadiyah Jember, 2024)
This research analyzes the determining factors of company performance included in the Indonesian Sharia Stock Index (ISSI). This research is a development of research regarding company performance using external audit quality, accounting information quality and earnings power as determinants. The development was carried out by refining the external audit quality variable proxy which initially only used dummy variables, so it was developed using 4 proxies, namely audit firm size, audit fees, non-audit service fees and audit partner tenure. Apart from that, this research carried out developments by adding control variables in the form of Operating Cash Flow, Revenue Growth and Company Losses. This research is based on Agency Theory, a theory in finance which states that conflicts of interest occur in company management. Managers are obliged to maintain the company's performance well in the eyes of investors. The population and research sample are public companies included in the ISSI. The research method used is Quantitative Research with the Patial Least Square (PLS) analysis technique. The variable that contributes significantly to Company Performance (KP) is Earnings Strength (KL) with a coefficient of -1.004 and p-value 0.001. The moderating variables that contribute are LAGROE on the KAE route to KP and KL to KP with coefficients of -0.112 and -0.107 with p-values of 0.005 and 0.007. Apart from that, the moderating variables that contribute are PP on the KAE route to KP and KIA to KP with coefficients of -0.123 and 0.109 with p-values of 0.002 and 0.006.